Republic of Serbia : First Review under the Policy Coordination Instrument -Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
An economic recovery is underway on the heels of the authorities' large and timely policy response. By 1Q2021, GDP exceeded its pre-crisis level and growth in 2021 is expected to reach 6.5 percent, supporting a smaller-than-expected fiscal deficit. Headline inflation increased above the 4.5 percent upper limit of the target band in September and October. Regulated energy prices for consumers are not expected to change until next spring, but electricity prices for corporates are set to increase. A new pandemic wave that started in late-July persists though activity seems to have decoupled from infections. With a gradual normalization of demand and supply conditions, growth is projected to reach 4.5 percent in 2022. Inflation is expected to revert to the lower half of the inflation tolerance band in 2H2022 as the effects from this year's drought wane and energy prices stabilize.